Macromedia Flash 8: Learning Media to Enhance Students' Understanding of Chemical Bonding - Haqqi Annazili Nasution; Syah Nurul Riswana; Ekin Dwi Arif Kurniawan (Department of Chemistry, Universitas Negeri Malang, 2025)
This study aims to examine the effect of Macromedia Flash 8-based learning media on students’ learning outcomes in the topic of chemical bonding. The research employed a quasi-experimental design with a pretest-posttest control group, involving two randomly selected classes from a public secondary school in Medan. The experimental class was taught using interactive media developed with Macromedia Flash 8, while the control class received instruction using conventional PowerPoint-based methods. Both classes were instructed using the Discovery Learning model to ensure consistency in pedagogy. A multiple-choice test served as the research instrument and was administered to both groups as a pretest and a posttest. The collected data were analyzed using normality and homogeneity tests, N-Gain calculations, and a one-tailed t-test to determine statistical significance. The results indicated a significant improvement in students’ learning outcomes in the experimental class compared to the control class, based on the N-Gain value (0.64) compared to the control class (0.56). These findings suggest that using Macromedia Flash 8 enhances students’ conceptual understanding and engagement, particularly in abstract topics such as chemical bonding. The interactive animations and visual elements embedded in the media helped bridge the gap between microscopic chemical representations and student comprehension. Therefore, integrating multimedia learning tools in chemistry instruction can contribute to more effective teaching and improved student performance.References Akaygun, S., & Jones, L. L. (2014). How does level of guidance affect understanding when students use a dynamic simulation of liquid–vapor equilibrium? In Learning with understanding in the chemistry classroom (pp. 243–263). Springer. Al-Muqtafa, A. K. (2019). Penggunaan Media Macromedia Flash 8 dalam Pembelajaran Baca Tulis Al-Quran di Kelas X MM SMK Al Hidayah Wonorejo Pasuruan. Jurnal Mu’allim, 1(1), 161–174. Ardac, D., & Akaygun, S. (2004). Effectiveness of multimedia‐based instruction that emphasizes molecular representations on students’ understanding of chemical change. Journal of Research in Science Teaching, 41(4), 317–337. Ayittey, R. F., Azumah, D. A., Amponsah, K. D., & Commey-Mintah, P. (2023). Withdrawn: Effectiveness of Multimedia versus Traditional Teaching Methods on Chemistry Practical Performance among Senior High School Students in Ghana. Chiu, T. K. F., Lin, T.-J., & Lonka, K. (2021). Motivating online learning: The challenges of COVID-19 and beyond. The Asia-Pacific Education Researcher, 30(3), 187–190. Creswell, J. W., & Creswell, J. D. (2017). Research design: Qualitative, quantitative, and mixed methods approaches. Sage publications. Demelash, M., Andargie, D., & Belachew, W. (2024). Enhancing Secondary School Students’ Engagement in Chemistry through 7E Context-Based Instructional Strategy Supported with Simulation. Pedagogical Research, 9(2). Dori, Y. J., & Barak, M. (2001). Virtual and physical molecular modeling: Fostering model perception and spatial understanding. Journal of Educational Technology & Society, 4(1), 61–74. Fraenkel, J., Wallen, N., & Hyun, H. (2019). How to Design and Evaluate Research in Education 10th ed. McGraw-Hill Education. Hake, R. R. (1998). Interactive-engagement versus traditional methods: A six-thousand-student survey of mechanics test data for introductory physics courses. American Journal of Physics, 66(1), 64–74. Harrison, A. G., & Treagust, D. F. (2000). Learning about atoms, molecules, and chemical bonds: A case study of multiple‐model use in grade 11 chemistry. Science Education, 84(3), 352–381. Huk, T. (2006). Who benefits from learning with 3D models? The case of spatial ability. Journal of Computer Assisted Learning, 22(6), 392–404. Izzati, N., Sukarno, S., & Rahim, A. (2022). Penerapan Model Discovery Learning Berbantukan Macromedia Flash 8 untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPA. Physics and Science Education Journal (PSEJ), 116–121. Jaber, L. Z., & BouJaoude, S. (2012). A macro–micro–symbolic teaching to promote relational understanding of chemical reactions. International Journal of Science Education, 34(7), 973–998. Karpudewan, M., Roth, W.-M., & Abdullah, M. N. S. Bin. (2015). Enhancing primary school students’ knowledge about global warming and environmental attitude using climate change activities. International Journal of Science Education, 37(1), 31–54. Kelly, R. M., & Jones, L. L. (2007). Exploring how different features of animations of sodium chloride dissolution affect students’ explanations. Journal of Science Education and Technology, 16, 413–429. Kotimah, E. K. (2024). Efektivitas Media Pembelajaran AudiovisualBerupa Video Animasi Berbasis Powtoon Dalam Pembelajaran Ipa. Katera: Jurnal Sains Dan Teknologi, 1(1), 5–12. Kozma, R. B. (1994). Will media influence learning? Reframing the debate. Educational Technology Research and Development, 42(2), 7–19. Kozma, R., & Russell, J. (2005). Students becoming chemists: Developing representational competence. Visualization in Science Education, 1, 121–146. Kurniawan, E. D. A., Muhaimin, & Syahri, W. (2016). Pengembangan media Pembelajaran Komik Kimia Menggunakan 3D Page Flip Untuk Materi Ikatan Kimia Siswa SMA Negeri 10 Kota Jambi. Unesa Journal of Chemical Education, 5. Mayer, R. E. (2002). Multimedia learning. In Psychology of learning and motivation (Vol. 41, pp. 85–139). Elsevier. Mayer, R. E. (2017). Using multimedia for e‐learning. Journal of Computer Assisted Learning, 33(5), 403–423. Muljana, P. S., Selco, J., Feldman, R., Gaston, T., & Choi, B. (2020). When chemical bonding is perceived simple and interesting: The design and development of a learning object. International Journal of Designs for Learning, 11(3), 148–161. Nasution, H. A., Darmana, A., & Syuhada, F. A. (2022). Development of Higher Order Thinking Skill (HOTS) Chemistry Module Based on Problem Based Learning (PBL) Model on Colligative Properties of Solutions. 1–5. https://doi.org/10.4108/eai.11-10-2022.2325340 Oladejo, A. (2022). Approaches to Teaching Chemistry. Available at SSRN 4124306. Plass, J. L., Mayer, R. E., & Homer, B. D. (2020). Handbook of game-based learning. Mit Press. Putra, R. F. (2021). Effect of Using Guided Inquiry-Based Chemical Bonding Modules on Student Learning Outcomes. Journal of Physics: Conference Series, 1788(1), 12022. Rahayu, S., Treagust, D. F., & Chandrasegaran, A. L. (2022). High school and preservice chemistry teacher education students’ understanding of voltaic and electrolytic cell concepts: evidence of consistent learning difficulties across years. International Journal of Science and Mathematics Education, 20(8), 1859–1882. Rutten, N., Van Joolingen, W. R., & Van Der Veen, J. T. (2012). The learning effects of computer simulations in science education. Computers & Education, 58(1), 136–153. Ryan, R. M., & Deci, E. L. (2000). Self-determination theory and the facilitation of intrinsic motivation, social development, and well-being. American Psychologist, 55(1), 68. Salta, K., & Koulougliotis, D. (2020). Domain specificity of motivation: chemistry and physics learning among undergraduate students of three academic majors. International Journal of Science Education, 42(2), 253–270. Sari, N., & Yenti, E. (2022). Pengembangan Media Pembelajaran Animasi dengan Macromedia Flash 8 Pada Materi Jenis-Jenis Koloid. Journal of Chemistry Education and Integration, 1(2), 74–80. Sweller, J. (2011). Cognitive load theory. In Psychology of learning and motivation (Vol. 55, pp. 37–76). Elsevier. Taher, R., & Bentri, A. (2024). Development of Interactive Media Using Macromedia Flash 8 Software in Natural Sciences Subjects in Elementary Schools. AL-ISHLAH: Jurnal Pendidikan, 16(2), 2339–2349. Titilade, A., Rilwanu, S., & Rabiu, S.R. (2024). Bridging the gap: Combining traditional teaching methods with a modern E-learning system for chemistry education in federal college of education Katsina. World Journal of Advanced Engineering Technology and Sciences, 12(2), 691–698. https://doi.org/10.30574/wjaets.2024.12.2.0301 Varadila, J., Meilisa, R., Annisa, A., & Folkourng, F. (2023). Development of learning media based on macromedia flash 8 to see learning outcomes and achievements in vocational high school students. Journal of Computer-Based Instructional Media, 1(1), 9–18. Waruwu, A. B. C., & Sitinjak, D. (2022). Penggunaan Multimedia Interaktif dalam Meningkatkan Minat Belajar Siswa pada Pembelajaran Kimia. Jurnal Pendidikan Mipa, 12(2), 298–305. Widarti, H. R., Nuriyanti, D., Sari, M. E. F., Wiyarsi, A., Yamtinah, S., & Rokhim, D. A. (2024). Identification of learning difficulties and misconceptions of chemical bonding material: A review. Eclética Química, 49. Wijaya, W. U. (2020). Analisis Kebutuhan Untuk Mengembangkan Media Video Animasi Pada Materi Struktur Atom Dan Ikatan Kimia. Journal of Tropical Chemistry Research and Education, 2(2), 59–67. Wu, H., & Shah, P. (2004). Exploring visuospatial thinking in chemistry learning. Science Education, 88(3), 465–492.